Speech model «constructions with modal lexemes need, must» as a way of indirect expression of motivation in literary text - Mikhalchuk, Natalia A. (Journal of the Belarusian State University. Philology, 2025)
It is demonstrated that the frequency of use the speech model of indirect expression of motivation «constructions with lexemes need, must» in literary text, as well as the choice of specific incentive meanings and methods of speech formulation are influenced by the following factors: the theme of the text, the writer’s poetics, the type of depicted linguistic personalities, their social affiliation, the historical era of writing the work, which determined the social system of values, the situation in the political, cultural and economic spheres of life. The specific representation of this speech model in Russian prose of the 20th and 21st centuries is revealed.
Keywords: indirect communication; indirect expression of motivation; communicative intention